ASSESSMENT OF KNOWLEDGE AND REASONS FOR MEDICATION NON-ADHERENCE IN AMBULATORY ELDERLY PATIENTS WITH HYPERTENSION AND DIABETES MELLITUS IN A GERIATRIC CENTRE IN NIGERIA (2021)
Introduction: Hypertension and type 2 Diabetes mellitus are global health disorders afflicting millions of elderly patients worldwide with an ever-increasing incidence and prevalence. Non-adherence to medications affects the quality and length of life, and has been associated with negative health outcomes and increasing healthcare costs especially in the elderly [1]. Few empirical data exist on the knowledge and medication adherence among elderly patients in sub-Saharan Africa countries. Aim: This study aimed to assess the knowledge, medication adherence, and the factors associated with patient’s knowledge on diabetes mellitus and hypertension. Methods: A cross-sectional study of 423 elderly patients aged ≥60 years diagnosed with hypertension and diabetes mellitus, selected consecutively at the Geriatric centre in the University College Teaching Hospital, Ibadan was carried out between October 2019 and January 2020. Sociodemographic information, knowledge of the indication of the medications, possible side effects, and details of medication adherence level with reasons for non-adherence were obtained using interviewer-administered semi-structured questionnaire. Bivariate and multivariate analyses were carried out using SPSS 23. Alpha was set at 0.05. Results: The mean age (±SD) of the older patients was 69.6 ± 6.4 years and 253 (59.8%) were females. About three-quarter of participants (320; 75.7%) were retired. Majority of the elderly (381; 90.1%) were hypertensive, while 270 (63.8 %) were diabetic, and 85 (20.1%) had multimorbidity of both hypertension and diabetes mellitus. Patients that were non-adherent with their medication were 138 (32.6%). The most common reasons reported for non-adherence included patient slept off (41; 56.6%), preoccupation (24; 33.1%) and unavailability of medications (12; 16.6%). Thirty-seven (8.7%) participants intentionally missed doses, out of which 22 (59.5%) reported pill burden as its reason for medication non-adherence. All patients 423 (100.0%) knew the indication for their medications and 20 (4.7%) experienced medication-related side effects. Overall, 299 (70.6%) and 309 (73.0%) of patients with hypertension and diabetes mellitus showed good knowledge about their conditions. Adherence to medication was associated with good knowledge in hypertensive patients (p=0.002), while being male (p=0.002), age-group of 60–69 (p=0.001) and poor adherence (p=0.001) were associated with good knowledge in diabetes mellitus patients. Conclusion: We found non-adherence was mainly as a result of patients’ behaviors, attitude, and unavailability of medications which could be the cause of low medication adherence among the elderly patients. A systematic review on factors associated with medication adherence in older patients reported medication review aimed at simplifying regimens and educating patients about their treatment as intervention to improve adherence [2]. Thus, we recommend educational intervention among the elderly patients. The elderly patients demonstrated good knowledge about their conditions and medication. However, the relatively good knowledge did not appear to have significant impact on patient’s adherence to medication. Improvement in medication adherence through interdisciplinary approach may improve clinical outcomes.